2020
DOI: 10.3389/fonc.2020.592706
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Sensitizes Cisplatin-Resistant Human Cervical Cancer Cells to Cisplatin Treatment: Involvement of Mitochondrial and NF-Kappa B Pathways

Abstract: BackgroundCervical cancer continues to be a major public health problem worldwide, and Cisplatin is used as first-line chemotherapy for this cancer; however, malignant cells exposed to CISplatin (CIS) become insensitive to the effects of this drug. PenToXifylline (PTX) is a xanthine that sensitizes several types of tumor cells to apoptosis induced by antitumor drugs, such as Adriamycin, Carboplatin, and CIS. The effects of PTX on tumor cells have been related to the disruption of the NF-κB pathway, thus preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
(57 reference statements)
0
7
1
Order By: Relevance
“…Our results suggest that the regulation of miR27a by the p38 pathway may occur at the transcriptional level, but the direct regulatory factors have not been found yet, and we will further explore it in future studies. However, although NF‐κB has been reported to be involved in many biological processes in many literatures, 47 , 48 our results show that NFκB inhibitors only increase the expression of the precursor miR27a, but have no significant effect on miR27a, this may be due to the shear and degradation of the precursor miR27a. Interestingly, TNF‐α is an important factor in disc degeneration 49 , 50 ; thus, these results suggest that TNF‐α induces apoptosis, the inflammatory response and extracellular matrix degradation and promotes FSTL1 expression when IDD occurs.…”
Section: Discussioncontrasting
confidence: 57%
“…Our results suggest that the regulation of miR27a by the p38 pathway may occur at the transcriptional level, but the direct regulatory factors have not been found yet, and we will further explore it in future studies. However, although NF‐κB has been reported to be involved in many biological processes in many literatures, 47 , 48 our results show that NFκB inhibitors only increase the expression of the precursor miR27a, but have no significant effect on miR27a, this may be due to the shear and degradation of the precursor miR27a. Interestingly, TNF‐α is an important factor in disc degeneration 49 , 50 ; thus, these results suggest that TNF‐α induces apoptosis, the inflammatory response and extracellular matrix degradation and promotes FSTL1 expression when IDD occurs.…”
Section: Discussioncontrasting
confidence: 57%
“…As shown in Figure 4A , the therapeutic effect of DDP on A2780/DDP cells was significantly reduced (IC 50 = 10.91 × 0.67 ppm), whereas that on parental A2780 cells remained sensitive (IC 50 = 1.94 × 0.17 ppm). According to previous studies, resistant cells generally upregulate intracellular GSH to inactivate DDP with GS-Pt adducts ( Levy et al, 2019 ; Bravo-Cuellar et al, 2020 ; Xu et al, 2020 ). As shown in Figure 4B , A2780/DDP cells were characterized by higher expression levels of GSH similar to those previously reported ( Xu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 96%
“…The results showed that differentially expressed genes were mainly enriched in the NF-κB signaling pathway. A previous study has found that adding carboplatin to cervical cancer SiHa and CaSki cells can activate the NF-κB signaling pathway and induce the expression of NF-κB ( 27 ). Our Western blot results also found that in EOC carboplatin-resistant cells, the nuclear expression of NF-κB p65 was significantly increased, and the expression of IκBα was significantly reduced, indicating that the up-regulation of NF-κB may inhibit EOC carboplatin sensitivity.…”
Section: Discussionmentioning
confidence: 99%